TEACHING LANGUAGE WITHOUT TRANSLATION FOR ADULT LEARNERS - Sarsenbayeva Mariya Agatovna (Journals Park Publishing, 2025)
In particular, this article covers the following: organic comprehension which is to absorb language directly without translation; This article examines how language is processed by our brains, the advantages of immersion, and methods for understanding meaning without the use of translation; Benefits of understanding without translation; Teaching a language without translation strategies.
Keywords: Context-Based Learning, Immersive Listening and Reading, native speakers, Monolingual Dictionaries.